1986
DOI: 10.1083/jcb.103.2.571
|View full text |Cite
|
Sign up to set email alerts
|

The acetylation of alpha-tubulin and its relationship to the assembly and disassembly of microtubules.

Abstract: Abstract.A tight association between Chlamydomonas alpha-tubulin acetyltransferase (TAT) and flagellar axonemes, and the cytoplasmic localization of both tubulin deacetylase (TDA) and an inhibitor of tubulin acetylation have been demonstrated by the use of calf brain tubulin as substrate for these enzymes. A major axonemal TAT of 130 kD has been solubilized by high salt treatment, purified, and characterized. Using the Chlamydomonas TAT with brain mbulin as substrate, we have studied the effects of acetylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(188 citation statements)
references
References 18 publications
(28 reference statements)
10
173
0
2
Order By: Relevance
“…4D). In addition, we found that αTAT1 does not acetylate tubulin dimers as efficiently as it does intact microtubules, consistent with previous αTAT1 studies (18,19) (Fig. 4E, blue).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…4D). In addition, we found that αTAT1 does not acetylate tubulin dimers as efficiently as it does intact microtubules, consistent with previous αTAT1 studies (18,19) (Fig. 4E, blue).…”
Section: Resultssupporting
confidence: 80%
“…There are several potential mechanisms for how αTAT1 may access the acetylation site on the inside of the microtubule lumen: by copolymerization with tubulin at growing microtubule plus-ends (15), by transient openings in the lattice during microtubule breathing (13,16,17), or by microtubule end-entry (12,18). Copolymerization is not likely to be the primary mechanism for αTAT1 access, because stable microtubules are acetylated, and because αTAT1 is more active on polymerized microtubules than on free tubulin dimers (12,13,(19)(20)(21)(22)(23)(24)(25). Conversely, the other modes of access are possible (12,13,18).…”
mentioning
confidence: 99%
“…4a,b). Physiologically, acetylation of tubulin occurs preferentially on polymerized MT 33 , whereas deacetylation of a-tubulin by HDAC6 is thought to occur when a-tubulin is in a heterodimeric state 34 . Therefore, HDAC6 might be a target of Ab, translating its effect on tubulin acetylation.…”
Section: Ab Increases Mt Dynamics and Increases Acetylated Tubulinmentioning
confidence: 99%
“…Acetylation of tubulin has been shown to occur preferentially on preformed microtubules, rather than on free tubulin dimers (Maruta et al, 1986;Black et al, 1989). The site of acetylation then must be accessible on the surface of microtubules.…”
Section: Discussionmentioning
confidence: 99%